Information Spillover, Volatility and the Currency Markets for the Binary Choice Model - Walid Ben Omrane; Christian M. Hafner (International Econometric Review (IER), 2009)
We use an impulse response methodology to analyse the effects of U.S. macroeconomic news announcements on the volatilities of three major exchange rates (Euro, Pound Sterling and Yen). Our data consist of 5 minute returns on exchange rates as well as the times of news announcements. In the definition of impulse responses, we allow for different types of news, and consider two categories in the application: those considered positive or negative for the U.S. economy. Using a multivariate GARCH model with exogenous news effects, we find that the initial impact of positive news on the volatility of the Pound is higher than that of the Euro, whereas the persistence of shocks is highest for the Yen. For negative news, we find that an important part of the impact on the Yen and Pound is induced by volatility spillover from the Euro.
Keywords: C32; C53; F31; 330; Information; Volatility; Impulse Response Function; Foreign Exchange